Dada and surrealism: A very short introduction - Hopkins, David (Oxford Oxford university press, 2004)
The avant-garde movements of Dada and Surrealism continue to have a huge influence on cultural practice, especially in contemporary art, with its obsession with sexuality, fetishism, and shock tactics. In this new treatment of the subject, Hopkins focuses on the many debates surrounding these movements: the Marquis de Sade's Surrealist deification, issues of quality (How good is Dali?), the idea of the 'readymade', attitudes towards the city, the impact of Freud, attitudes to women, fetishism, and primitivism. The international nature of these movements is examined, covering the cities of Zurich, New York, Berlin, Cologne, Barcelona, Paris, London, and recently discovered examples in Eastern Europe.Hopkins explores the huge range of media employed by both Dada and Surrealism (collage, painting, found objects, performance art, photography, film) , whilst at the same time establishing the aesthetic differences between the movements. He also examines the Dadaist obsession with the body-as-mechanism in relation to the Surrealists' return to the fetishized/eroticized body.